Comunicación alternativa y jóvenes :"Evaluación de la experiencia del proyecto Latacunga desde adentro". - Merino Páez, Verónica Jasmín (2020)
The present work is focused on evaluating the experience of the formative research project: Latacunga From Inside (LDA), taking as a case study the Miguel Iturralde Educational Unit, in the city of Latacunga. This through the application of a qualitative methodology, since the techniques of the focus group, in-depth interviews and structured observation were used, the main objective being to carry out an evaluation of the project and its results in the creation of alternative communication media. The analysis of the information was developed by means of the instruments elaborated in each technique, for this a sample was obtained by non-probabilistic selection, of the direct participants within the educational establishment and their guides. In addition, the digital magazine Miguelito comunica was analyzed, identifying that in general it complies with the parameters defined by the LDA project. Among the main findings, it is established that the project managed to incorporate the students of the establishment, in the construction of a type of inclusive communication that promotes the validity of human rights